Implementation of Problem-Based Learning Assisted by PhET Simulation to Improve Students’ Understanding of Mirror Concepts and Learning Engagement - Rizal Eko Zulianto; Ani Rusilowati; Sarwi Sarwi (Universitas Negeri Semarang, 2025)
Physics is one of the subjects that students find difficult to understand. Physics is not only a science that requires memorization, but also requires a deep understanding of its concepts. Physics studies natural phenomena physically and is written in mathematical form, thus emphasizing the aspect of conceptual understanding. In addition to conceptual understanding, another important aspect is student involvement in the learning process. One important topic that needs to be studied is mirrors. The topic of mirrors will be easier to understand if it is practiced so that students can understand it better. Therefore, Phet simulation media is needed. The purpose of this study is to explain the differences in understanding the concept of mirrors between students who use PBL plus PhET and students who use regular PBL, as well as to analyze the differences in student engagement in learning about mirrors between students who use PBL plus PhET and students who use regular PBL. The population in this study consisted of 64 students from MA Mathalibul Huda and 64 students from MA Darul Hikmah Menganti. Data collection methods included tests, observations, and documentation. The collected data were analyzed using N-Gain and t-tests. Based on the research results, there is a difference in concept comprehension between the PBL Plus and regular PBL learning models, with the PBL Plus class achieving a higher average post-test score of 81.03, while the regular PBL class achieved an average post-test score of 62.31. The N-Gain value - Gain of the regular PBL class was 0.22, while the N-Gain value of the PBL Plus class was 0.58, which is categorized as moderate. The T-test resulted in a sig value (2-tailed) of 0.00 < 0.05. Thus, it can be concluded that the PBL Plus learning model is effective in improving students’ conceptual understanding of mirror material. In addition, there is also a difference in student learning engagement between the PBL Plus class and the regular PBL class, where PBL Plus shows that the category of active students is higher than that of the regular PBL class based on 4 indicators of student learning engagement.